GREENR: Global Reference for Environment, Energy, and Natural Resources. - Quinn, Mary Ellen (Booklist, 2010)
The article presents an evaluation of the online reference database GREENR: Global Reference for Environment, Energy, and Natural Resource, available from the publisher Gale, a division of Cengage Learning Inc.